Seamless handover in urban 5G-UAV systems using entropy weighted method - Warrier, Anirudh; Al-Rubaye, Saba; Panagiotakopoulos, Dimitrios; Inalhan, Gokhan; Tsourdos, Antonios (World Academy of Science, Engineering and Technology, 2021)
The demand for increased data transfer rate and network traffic capacity has given rise to the concept of heterogeneous networks. Heterogeneous networks are wireless networks, consisting of devices using different underlying radio access technologies (RAT). For Unmanned Aerial Vehicles (UAVs) this enhanced data rate and network capacity is even more critical especially in their applications of medicine, delivery missions and military. In an urban heterogeneous network environment, the UAVs must be able switch seamlessly from one base station(BS) to another for maintaining a reliable link. Therefore, seamless handover in such urban environments have become a major challenge. In this paper, a novel scheme to achieve seamless handover is developed, an algorithm based on Received Signal Strength (RSS) criterion for network selection is used and Entropy Weighted Method (EWM) is implemented for decision making. Seamless handover using EWM decision-making is demonstrated successfully for a UAV moving across fifth generation(5G) and long-term evolution (LTE) networks via a simulation level analysis. Thus, a solution for UAV-5G communication, specifically the mobility challenge in heterogeneous networks is solved and this work could act as step forward in making UAV-5G architecture integration a possibility.
Keywords: air to ground (A2G); fifth generation(5G); handover; mobility; unmanned aerial vehicle (UAV); urban environments